Forma organizacyjno-prawna i rodzaj prowadzonych ubezpieczeń jako determinanty działalności inwestycyjnej zakładów ubezpieczeń - Szkarłat, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper examines internal determinants such as legal form of insurance company and type of insurance business that impact the asset allocation decision of insurance companies. Insurance sector in Poland is highly regulated and is subject to stringent asset allocation constraints. Within these constraints, I analyze internal factors influencing the decisions to make changes in the composition of aggregate holdings of bonds, stocks, commercial papers, real estate, bank deposit and mortages. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 424-433